Geometric Shaping for Distortion-Limited Intensity Modulation/Direct Detection Data Center Links - Ethan M. Liang; Joseph M. Kahn (IEEE Photonics Journal, 2023)
Intra-data center links are subject to transmission impairments that pose challenges for efficient scaling of per-wavelength data rates beyond 100 Gb/s. Limited electrical and optical component bandwidths, limited data converter resolution, and direct detection induce significant signal-dependent distortion, degrading receiver sensitivity (RS) and chromatic dispersion tolerance. In this paper, we present a geometric shaping (GS) scheme that optimizes transmitted intensity levels based on symbol-error statistics observed at the receiver. The proposed GS scheme adjusts these levels to achieve substantially equal symbol-error probabilities at all decision thresholds. The scheme enables the levels most affected by signal-dependent distortion to be detected with the same reliability as other levels, thereby increasing the effectiveness of linear or nonlinear equalization techniques. This can be exploited to improve RS and extend transmission distance for a fixed equalization scheme or, alternatively, to reduce the complexity of signal processing needed to achieve a target RS or transmission distance. For example, in 200 Gb/s PAM links, GS and 21-tap linear equalization achieves RS and reach similar to uniform level spacing and Volterra nonlinear equalization with 21 linear and 3 second-order taps.